Government Communication Management Strategy - Muhamad Akasah (Institute of Computer Science (IOCS), 2022)
Basically, this research aims to determine the extent to which communication management strategies are involved within the scope of the government/public world in Indonesia. The notion of government communication is communication between humans (human communication) that occurs in the context of government organizations. Therefore, government communication cannot be separated from the context of organizational communication and it is also part of organizational communication. The flow of sending and receiving messages is carried out through a network whose nature of the relationship is mutually dependent on each other based on formal rules. The messages sent and received are not only in the form of information, but also the dissemination of ideas, instructions, or feelings related to government actions and policies. In addition, government communication is also one of the important elements in public organizations, namely being part of organizational communication, where government communication can be separated from internal and external communications. Once again communication is an important element in government organizations where communication is considered as the heart of the organization so that without communication there is no organizational activity and this means that without communication the organization will die. In order for government communication to run well (effectively and on target), the government as the main actor who initiates communication, among others, needs to do the following things. First, choosing the right, among others, the language used (adjusted to the communicant). Second, trying to remove or minimize the communication barriers of crisis government. Third, mastering knowledge about effective communication practices that can help government administrators manage more effectively, such as knowledge of the audience. And lastly, government communication is required to change the government's approach to public information from traditional to professional strategic communication processes that specifically control the flow of news.